Sistema de controle baseado em psicrometria aplicado à sistemas HVAC: estudo de caso, sala limpa do Instituto itt Chip / UNISINOS - Pereira, Tiago Anacleto (Universidade do Vale do Rio dos Sinos, 2019)
The present work presents the development of a new control system based on psychrometrics applied to HVAC (Heating, Ventilation, and Air Conditioning) systems. The purpose aims to reduce the energy consumption of the HVAC system of a cleanroom of the Technological Institute in Semiconductors - ITT Chip / UNISINOS. The study reviews the fundamentals and principles of psychometrics, a literature review, the audit of control engineering and automation of the legacy system, the development, and integration of a supervisory system, and the development of the proposed control structure of the system. This system consists of a structured control logic that determines based on the calculation of enthalpies and thermal loads the reference values for the PID controllers and the cycle condition that the system must operate. The tuning of the PID controller parameters was performed based on the process models. An analysis of the proposed control system performance against reference tracking and disturbance rejection under different scenarios as well as an analysis of energy consumption is performed and compared with the legacy system. The results reveal the effectiveness of the proposed system due to its superior performance and lower power consumption compared to the legacy system.
Keywords: HVAC; Controle PID; Psicrometria; Sala limpa; ACCNPQ::Engenharias::Engenharia Elétrica